Implementasi Pembelajaran Pendidikan Agama Islam Bagi Siswa Berkebutuhan Khusus (Studi Kasus : SlB ‘Aisyiyah Tembung) - Mavianti Mavianti; Rizka Harfiani (Al-Ulum: Jurnal Pendidikan Islam, 2020)
Abstract: The purpose of this study is to describe and analyze the implementation of Islamic religious education learning for students with special needs (case study: SLB ‘Aisyiyah, Tembung). This research uses a qualitative approach, with descriptive research type. Data collection techniques using observation, interviews, and documentation. The data analysis technique used is descriptive qualitative analysis. The results showed that the learning of Islamic education uses systematic learning planning that involves related elements according to competence to support the success of learning. Furthermore, the learning process is designed attractively to foster student interest in learning. In addition, students are also given motivation to want to excel in accordance with the abilities of each student. Keywords : Implementation, PAI Learning, Special Needs